A phase I/II clinical trial for the hybrid of intracavitary and interstitial brachytherapy for locally advanced cervical cancer. Issue 1 (December 2016) - Murakami, Naoya; Kato, Shingo; Nakano, Takashi; Uno, Takashi; Yamanaka, Takeharu; Sakurai, Hideyuki; Yoshimura, Ryoichi; Hiratsuka, Junichi; Kuroda, Yuki; Yoshio, Kotaro; Itami, Jun
Abstract Background This paper describes about a study protocol of phase I/II multicenter prospective clinical trial evaluating the feasibility and efficacy of the hybrid of intracavitary and interstitial brachytherapy (HBT) for locally advanced uterine cervical cancer patients. Methods and design Patients with histologically confirmed FIGO stage IB2, IIA2, IIB, and IIIB uterine cervical carcinoma width of which is larger than 5 cm assessed by MRI will be entered to this clinical trial. Protocol therapy is 30-30.6 Gy in 15-17 fractions of whole pelvic radiotherapy concurrent with weekly CDDP (40 mg/m2 ), followed by 24 Gy in 4 fractions of HBT and central shield EBRT up to 50-50.4 Gy in 25-28 fractions. Tumor width is assessed again within one week before the first HBT and if the tumor width is larger than 4 cm, patients proceed to the secondary registration. In phase I section, feasibility of this will be investigated. If less than 10 % out of 20 patients experienced greater than grade 3 acute non-hematologic adverse effects, the study proceeds to phase II part. In phase II part a total of 55 patients will be accrued and the efficacy of the HBT will be investigated comparing with historical control data. If the lower margin of 90 % confidence interval of the 2-year pelvic progression-free survival of the HBT trial is higher than 64 %, the HBT is considered to be more effective than conventional ICBT. Discussion The aim of this study is to demonstrate the feasibility and efficacy of the HBT for locally advanced cervical cancer. This trial will clarify the indication, feasibility, and efficacy of this new technique. Trial registration UMIN000019081 ; Registration date: 2015/9/30